Assessing the Knowledge and Practices of Anganwadi Workers Regarding Integrated Child Development Services - Preeti,; , Vandana Varma; , Ella Rani (Archives of Current Research International, 2025)
The Integrated Child Development Services (ICDS) scheme plays an important role in improving the health, nutrition, and overall development of children and women in India. Anganwadi workers play a pivotal role in delivering the services at the grassroots level in India. The aim of the present study was to assess the knowledge and practices of Anganwadi workers in addressing health needs within rural communities. The study was conducted in two blocks of Hisar district in Haryana state. A sample of 100 Anganwadi workers was selected randomly by covering 10 villages. The research employed a mixed-methods approach, combining surveys and interviews with Anganwadi workers in diverse rural settings. It was found that the majority of Anganwadi workers had knowledge of developmental activities (84.40%), immunization (90.00%) and nutritional requirements for pregnant and lactating women (67.43%) and low knowledge of anthropometric measurements (30.75%). The study also revealed that knowledge was negatively correlated with age and working experience. This assessment helped gauge their capacity to provide accurate information and support to the community. The research findings had practical implications for policymakers, organizations and stakeholders involved in early childhood development and maternal health programs. By studying the profile, facility and knowledge of Anganwadi workers, this research contributes to the existing body of knowledge, addressing the strengths, challenges and areas for improvement within the workforce. Ultimately, the aim is to enhance the quality of services provided by Anganwadi workers and promote the holistic well-being of children and mothers in the community.